Radiation variation in electrical conductivity of calcium fluoride; Soviet Physics Journal; Vol. 15, № 5 - Zavadovskaya E. K.; Fedorov V. A.; Lisitsyna L. A.; Lisitsyn V. M. Viktor Mikhailovich (1972, 1972)
В фонде НТБ ТПУ отсутствует